Implementasi Nilai-Nilai Moderasi Beragama pada Anak Usia Dini: Studi Kasus KB PAUD Al-Aman Podosugih - Eri Sisca Amalia; Lintang Trisha Elmaga; Nabilah Hakimah Al Huda; Achmad Tubagus Surur (JOURNAL SAINS STUDENT RESEARCH, 2024)
. This research intends to investigate how values of religious moderation are applied in early childhood education at KB PAUD Al Aman Podosugih. Employing qualitative research technique, information was gathered from books, articles, observations, interviews, and records. The focus of the research includes the teacher’s strategy in teaching religious moderation, the role of parents in instilling these values, and the impact of their application on children’s attitudes and behavior. The results show that teachers use interactive learning methods and stories that reflect diversity to teach tolerance values. In addition, collaboration between teachers and parents is very important in supporting religious moderation education. The impact of implementing these values is seen in the increase in children’s tolerance and empathy attitudes, as well as a decrease in intolerant behavior. This study highlights the significance of the involvement of every participant in shaping a respectful and tolerant generation from an early age.